The Use of Code-Switching Method to Improve Female Students’ Speaking Skills - Nur Mina; Cut Mulia Zuhra; Nora Fitria (English LAnguage Study and TEaching, 2023)
Speaking is the way to express the idea with others in the social community. Many students still have difficulties in mastering speaking skills. This problem was also faced by the students of SMP Islam Ibnu Khaldun Banda Aceh in learning speaking. The reasons why they get difficulties in speaking include having lack of vocabularies to express idea and being not confidence to speak in English. Therefore, this research apllied code-switching method in speaking class in order to make the students easier to speak in English. This research was quantitave which is one group pretest-posttest design. The population of this research are all taken as the sample , which are 30 female students in the eighth grade of SMP Islam Ibnu Khaldun Banda Aceh. The data were gathered through test.. The data were analyzed after getting the score of the students’ test and processed by using t-test formula in SPSS version 23. The result showed that there was an improvement on students’ speaking skill after the implementation of code-switching method. The mean score of post-test was 49.07, while the pre-test was 27.73. Besides, the result of t-test showed that the score increased by about 21.34. Finally, from the explanation above it can be concluded that there was a significant difference between the students’ speaking achievement before and after teaching speaking by using code-switching method.